Analysis of Prospective Arabic Teachers’ Technological Pedagogical Content Knowledge (TPACK) - Zaimatuz Zakiyah; Muhammad Jafar Shodiq; Arrum Wijaya (LISANIA: Journal of Arabic Education and Literature, 2022)
21st-century learning requires teachers to integrate technology into learning. Therefore, teachers need to improve their professional abilities in using technology. This research was conducted to obtain the TPACK profile of prospective Arabic language teachers who are currently studying for undergraduate program at Arabic Education department of IAIN Pekalongan. Furthermore, this research is survey research. Accordingly, primary data was collected by distributing questionnaires. In addition, researchers also used observation and documentation. In general, the TPACK for prospective Arabic teachers is categorized as "good". Howevers, there are some aspects that need to be improved, namely Content Knowledge, Pedagogical Content Knowledge, and Technological Pedagogical Content Knowledge itself. In addition, each item with lower value than the total average of all aspects needs to be considered as well. In addition, the results of this analysis provide information related to the TPACK for prospective Arabic teachers that is useful as evaluation material for interested parties, such as Lembaga Pendidikan Tenaga Kependidikan (LPTK) as an institution in higher education that is assigned to prepare professional teachers.